1993
DOI: 10.1128/mcb.13.7.4039
|View full text |Cite
|
Sign up to set email alerts
|

SKN1 and KRE6 define a pair of functional homologs encoding putative membrane proteins involved in beta-glucan synthesis.

Abstract: KRE6 encodes a predicted type II membrane protein which, when disrupted, results in a slowly growing, killer toxin-resistant mutant possessing half the normal level of a structurally wild-type cell wall (1-->6)-beta-glucan (T. Roemer and H. Bussey, Proc. Natl. Acad. Sci. USA 88:11295-11299, 1991). The mutant phenotype and structure of the KRE6 gene product, Kre6p, suggest that it may be a beta-glucan synthase component, implying that (1-->6)-beta-glucan synthesis in Saccharomyces cerevisiae is functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 43 publications
4
99
0
Order By: Relevance
“…kre6D cells make half normal amounts of b1,6-glucan, whereas skn1D cells make b1,6-glucan normally and have no growth defect. Expressed at high copy, Skn1 restores almost normal levels of b1,6-glucan to kre6D cells, and kreD skn1D double mutants are inviable or very slow growing, depending on the strain background, and make no more than 10% of normal amounts of b1,6-glucan (Roemer et al 1993). From this, Kre6 and Skn1 seem to be functional homologs, with Kre6 normally having the dominant role in b1,6-glucan synthesis.…”
Section: B16-glucanmentioning
confidence: 95%
“…kre6D cells make half normal amounts of b1,6-glucan, whereas skn1D cells make b1,6-glucan normally and have no growth defect. Expressed at high copy, Skn1 restores almost normal levels of b1,6-glucan to kre6D cells, and kreD skn1D double mutants are inviable or very slow growing, depending on the strain background, and make no more than 10% of normal amounts of b1,6-glucan (Roemer et al 1993). From this, Kre6 and Skn1 seem to be functional homologs, with Kre6 normally having the dominant role in b1,6-glucan synthesis.…”
Section: B16-glucanmentioning
confidence: 95%
“…SKN1 was previously identified as a multicopy suppressor for the Dkre6 null phenotype, restoring defects in cell wall b-1,6-glucan synthesis and anchorage of cell wall proteins in Dkre6 disruptants [12]. Using hydrophobic cluster analysis, it was found that Kre6p and Skn1p show significant similarities to a family of 16 glycoside hydrolases, indicating that they are glucosyl hydrolases or transglucosylases [18].…”
Section: Discussionmentioning
confidence: 99%
“…or Dipt1 deletion mutant with SKN1 or IPT1 A Ycp50 plasmid bearing a functional SKN1 gene [12], was digested with SalI and EcoRI. The resulting 3.7 kb fragment with the SKN1 coding sequence was ligated into the yeast multicopy shuttle vector pRS423 [15], yielding the plasmid pRS423(SKN1).…”
Section: Complementation Of Dskn1mentioning
confidence: 99%
“…Null mutations in these genes disrupt the normal synthesis of //1,6-glucan in various ways leading to reduced levels of the polymer and a killer-resistant phenotype. Based on the molecular and genetic analyses of these kre null mutants, it has been suggested that //1,6-glucan is synthesized by a stepwise sequential process in the secretory pathway Roemer et al 1993). A few genes implicated in fl,3-glucan synthesis have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…KRE5 encodes a potential endoplasmic reticulum (ER) protein essential for//1,6-glucan synthesis (Meaden et al 1990). KRE6 and SKN1 are a pair of functional homologs coding for type II integral membrane proteins located in the Golgi apparatus (Roemer and Bussey 1991;Roemer et al 1993Roemer et al , 1994. KREll codes for a 63 KDa cytoplasmic protein .…”
Section: Introductionmentioning
confidence: 99%